"It puts a human face on the researched" – A qualitative evaluation of an Indigenous health research governance model. (10th August 2015) - Bond, Chelsea; Foley, Wendy; Askew, Deborah
Abstract: Objective: To describe the Inala Aboriginal and Torres Strait Islander Community Jury for Health Research, and evaluate its usefulness as a model of Indigenous research governance within an urban Indigenous primary health care service from the perspectives of jury members and researchers. Methods: Informed by a phenomenological approach and using narrative inquiry, a focus group was conducted with jury members and key informant interviews were undertaken with researchers who had presented to the Community Jury in its first year of operation. Results: The jury was a site of identity work for researchers and jury members, providing an opportunity to observe and affirm community cultural protocols. Although researchers and jury members had differing levels of research literacy, the jury processes enabled respectful communication and relationships to form, which positively influenced research practice, community aspirations and clinical care. Discussion: The jury processes facilitated transformative research practice among researchers and resulted in transference of power from researchers to the jury members, to the mutual benefit of both. Conclusion: Ethical Indigenous health research practice requires an engagement with Indigenous peoples and knowledge at the research governance level, not simply as subjects or objects of research.